2006
DOI: 10.1038/sj.tpj.6500419
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymorphism in the 17β-hydroxysteroid dehydrogenase type 5 (aldo-keto reductase 1C3) gene is associated with lower serum testosterone levels in caucasian men

Abstract: Genetic variation in the androgen metabolizing enzymes is important to identify and feature as they may influence the risk of prostate cancer and help clarify the etiology of the disease. Human 17b-hydroxysteroid dehydrogenase type 5 (AKR1C3) is highly expressed in the prostate gland and plays a major role in the formation and metabolism of androgens. We identified five novel polymorphisms in the AKR1C3 gene. One of those an A4G substitution in exon 2 that confers a Glu77Gly change occurred in 4.8% in Caucasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…1, Panel D). Jakobsson et al reported an association between the p.Glu77Gly polymorphism and lowered serum testosterone levels in men [67]. Functional analysis performed in the study also revealed a tendency for decreased activity of the polymorphic Gly77 enzyme, although this difference was not significant.…”
Section: Assessment Of the Impact Of Missense Substitutions On 17ˇ-hsmentioning
confidence: 53%
See 1 more Smart Citation
“…1, Panel D). Jakobsson et al reported an association between the p.Glu77Gly polymorphism and lowered serum testosterone levels in men [67]. Functional analysis performed in the study also revealed a tendency for decreased activity of the polymorphic Gly77 enzyme, although this difference was not significant.…”
Section: Assessment Of the Impact Of Missense Substitutions On 17ˇ-hsmentioning
confidence: 53%
“…1(Panels C and D), the current study shows a lack of effect of the p.His5Gln variation on enzymatic activity. Another non-synonymous variant, p.Glu77Gly, was previously reported to be associated with circulating testosterone levels [67]. As discussed previously, the assessment of the effect of this variant on the enzymatic activity of the 17␤-HSD type 5 enzyme revealed a slightly significant difference in the conversion levels of androstenedione as compared to the wild-type enzyme (Fig.…”
Section: Akr1c3/hsd17b5mentioning
confidence: 53%
“…We have reported previously from the EMAS cohort associations of the AR exon 1 CAG repeat polymorphism with endocrine and metabolic parameters (23), and of AR exon 1 CAG repeat and other polymorphisms with heel ultrasound parameters (8). Other genes with polymorphisms associated with androgen and/or estrogen levels in men include SHBG (28), CYP17 (29), CYP19A1 (30), 17␤HSD5 (31), and uridine diphosphate glucuronyltransferase 2B7 (UGT2B7) (32), but many potentially important polymorphic influences have apparently not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1C3 expression was observed to be most prominent in the prostate and mammary gland and is in the position to control estrogen action at the receptor level [39][40][41]. AKR1C3_rs7741 is in perfect LD with AKR1C3_rs3763676 (r 2 = 1.00), for which a lower transcriptional enzyme activity for minor allele carriers was observed [42]. Decreased activity of the enzyme leading to less reduction of estrone to 17b-estradiol appears compatible with our observation of a more pronounced risk increase associated with duration of monotherapy use in homozygous carriers of the minor A allele of AKR1C3_rs7741 (Table 3; Online Resources 3 and 5).…”
Section: Discussionmentioning
confidence: 99%